Association Between Career Plateau and Intention to Continue Working in the Current Position Among Mid-Career Nurses - Oga, Chizuko; Azuma, Tomomi (Journal of Japan Academy of Nursing Science, 2025)
Objective: To find an association between career plateau measurement scale scores and the intention to continue working in the current position among mid-career nurses.Methods: A total of 528 mid-career nurses underwent a survey on the intention to continue working in the current position and career plateau. The career plateau measurement scale for mid-career nurses was used to measure career plateau. The cutoff score of the scale for the intention to continue was calculated through receiver operating characteristic analysis and used to divide the nurses into “plateau group” and “non-plateau group.” Then, a binomial logistic regression analysis was conducted using the intention to continue working in the current position as a dependent variable and the presence or absence of a plateau or scale score and potential confounding factors as explanatory variables.Results: The career plateau was significantly associated with the intention to continue working in the current position (adjusted odds ratio 2.70, 95% confidence interval [CI] 1.83–3.98, p < 0.001). The scale scores were also significantly associated with the intention to continue working in the current position (adjusted odds ratio 0.97, 95% CI 0.95–0.98, p < 0.001).Conclusion: The career plateau measurement scale score for mid-career nurses may be a useful measure associated with the intention to continue working in the current position.